Atypical presentation of caroli’s syndrome: A case report (Indian Journal of Case Reports, 2019)
Caroli’s disease and Caroli’s syndrome are rare congenital disorders. Caroli’s disease is characterized by multiple sequential cystic or saccular dilatations of the large intrahepatic biliary ducts while Caroli’s syndrome has small bile duct involvement and congenital hepatic fibrosis. The incidence of Caroli’s disease is as low as 1/1,000,000 people. The average age of presentation is early adolescence. Magnetic resonance cholangiopancreatography is a most valuable investigation in diagnosis. Here, we report the case of Caroli’s Type II without renal involvement as late as 6 years of age with severe portal hypertension and hypersplenism. The child had no history of jaundice or recurrent abdominal pain in the past.